Assessment of Interleukin-1 Gene Cluster Polymorphisms in Lone Atrial Fibrillation: New Insight into the Role of Inflammation in Atrial Fibrillation - Çoker Gürkan, Ajda; Güngör, Barış; Ekmekçi, Ahmet; Arman, Ahmet; Özcan, Kazım S.; Üçer, Ekrem; Çalık, Nazmi; Yılmaz, Hale; Tezel, Tuna; Bolca, Osman (Wiley-Blackwell, 111 River St, Hoboken 07030-5774, Nj USA, 2013)
BackgroundSystemic inflammation is accepted as one of the pathophysiological mechanisms of atrial fibrillation (AF). The role of inflammation has been shown previously. Interleukin (IL) system is the main modulator of the inflammatory responses and genetic polymorphisms of IL-1 cluster genes are associated with increased risk for inflammatory diseases. ObjectivesTo investigate the association between polymorphisms of IL-1 cluster genes and lone AF. Subjects and MethodsDNA samples were collected from 70 proven lone AF patients and 70 healthy subjects. Genomic DNA was typed for the variable number of the tandem repeat (VNTR) IL-1 receptor antagonist (RN) gene polymorphism, IL-1B -511 C > T(rs16944) promoter polymorphism, and +3953 C > T(rs1143634) polymorphism in exon 5 by polymerase chain reaction. ResultsIn lone AF group the frequency of IL-1RN2/2 and IL-1RN1/2 genotypes were higher than in the control group (7.2% vs 4.3% and 48.5% vs 22.8%, respectively; (2) = 14.1; P = 0.028). The frequency of allele 2 was significantly higher in the lone AF group (32.1% vs 15.7%; (2) = 10.7; P = 0.005). Allele and genotype distribution of IL-1B -511 C > T and +3953 C > T polymorphisms were not statistically different between the groups. C-reactive protein (CRP) levels were higher in lone AF patients compared to the control group (median = 1.25, interquartile range [IQR] = 0.85 vs median = 1.08, IQR 0.46 mg/L, respectively; P = 0.02). In multivariate regression analysis, presence of allele 2 of IL-1 VNTR polymorphism and elevated plasma high-sensitive-CRP levels were the independent predictors of lone AF. ConclusionPresence of allele 2 of VNTR polymorphism of IL-1RN gene may cause increased risk for lone AF probably due to the inadequate limitation of inflammatory reactions.
Keywords: Lone Atrial Fibrillation; Interleukin Polymorphism; CRP; C-Reactive Protein; Coronary-Artery-Disease; Of-Function Mutation; Receptor Antagonist; Rheumatoid-Arthritis; Myocardial-Infarction; Ischemic-Stroke; In-Vitro; Risk; Anakinra; Yalnız Atriyal Fibrilasyon; Interlökin Polimorfizm; C-Reaktif Protein; Koroner Arter Hastalığı; Fonksiyon Değiştirme Mutasyonu; Reseptör Antagonisti; Miyokardiyal Enfarktüs; Iskemik İnme